Мікро- та наноелектромеханічні системи - Воловіков, Я. Т. (ХНУРЕ, 2025)
The rapid development of micro- and nanoelectromechanical systems (MEMS and NEMS) has significantly influenced various technological sectors, including biomedical engineering, telecommunications, aerospace, and robotics. These systems integrate mechanical and electronic components at microscale and nanoscale levels, enabling high precision, miniaturization, and energy efficiency. MEMS devices are widely applied in accelerometers, gyroscopes, and microfluidic systems, while NEMS technology is paving the way for quantum sensors, molecular-scale actuators, and next-generation computing. This study explores the advancements in MEMS and NEMS fabrication, their key applications, and future prospects in engineering and science
Keywords: наноелектромеханічна система; nanoelectromechanical system